Clusters como estratégia de desenvolvimento de pequenas e médias empresas: um estudo exploratório do caso moveleiro do município de Colatina - ES - Souza, Marcos Batista de (2003)
This work aims at showing that the formation of clusters of small and medium firms in the area of furniture can represent an important future economic alternative for Colatina. The main focus of this study aims to analyze the development of furniture companies of the county of Colatina, located in the center-west of the Espirito Santo. It intends to identify how these companies are organized which barriers are faced by them, when they seek forms guarantee competitiveness and which activities could be targeted of stimulus by the part of support institutions in order to transform this furniture region into a dynamic cluster and initiate a process of local development. I observe that Colatina constitutes an interesting case of study due the fact of accumulation of PMEs that, even having to face some obstacles, it is obtaining success to drive the local productive system and to attract investments.